Newmark’s Translation Methods in the Indonesian Translation of Risk It All by Bruno Mars - Humaira, Zulfa Alifah; Bustam, Muhammad Rayhan (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
This study aims to identify the Newmark translation method applied to the translation of the song lyrics “Risk It All” by Bruno Mars. The purpose of this identification is to determine whether the translator emphasizes or leans toward the source language (SL) or the target language (TL). The method used for this study is a descriptive qualitative approach, as it is considered appropriate for the study focus based on the characteristics, phenomena observed, and selected data. By comparing 20 lines of source language (English) and the target language (Indonesian) lyrics using Newmark’s theory, the results indicate four translation methods were employed: literal (35%), communicative (30%), free (30%), and lastly faithful (5%). Based on these percentages, it can be concluded that the translator tends to preserve the text structure of the English language while adapting aspects to ensure naturalness that is easily understood by the Indonesian as the target audience. Accuracy of meaning and aesthetic considerations regarding the song lyrics are taken into account to achieve an equivalent emotional impact for the listeners. Thus, this study is titled ‘Newmark’s Translation Methods in the Indonesian Translation of “Risk It All” by Bruno mars’. Keywords: Translation Methods, Newmark, Song Lyrics, Bruno Mars